The Implementation of Village’s Fund on Goods and Services Procurement - setyorini, christina tri (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Procurement of goods and services is an activity associated to meeting an agency or institution's needs and providing resources, whether in the form of commodities or services. The village is a government institution that procures goods and services in accordance with Head of LKPP Regulation No. 13 of 2013, as amended by Head of LKPP Regulation No. 22 of 2015 regarding procurement of goods and services in the village, and regent regulations as the implementation rules per regency where the village is located. The goal of this study was to identify the obstacles associated with implementing the procurement of goods and services in the village and the efforts made to overcome these obstacles. This study employed a qualitative approach and the case study method in six villages within the Banyumas Regency subdistrict of Sumbang. In this study, the triangulation method was implemented through semi-structured interviews, observation, and document examination. The results of the study indicate that executing goods and services procurement presents obstacles at all phases, including planning, handover, implementation, oversight, reporting, and accountability. The greatest issue is to the quality of the village infrastructure and the absence of oversight and socialization of procurement standards for goods and services. The stages of planning are crucial since this is when the priorities for spending local funds are selected. Planning errors have an effect on every subsequent procedure. This research has investigated the challenges of implementing procurement of goods and services in the village and can thus provide direction for strategies to improve the implementation of procurement of goods and services in the village. In addition, the government might use this study's findings to formulate village-related policies and continue to improve.